(untitled) (World Bulletin of Social Sciences, 2025)
This article provides a theoretical analysis of the concept of facilitative management, its essence, and its role in the activities of young leaders. The pedagogical and psychological aspects of developing competencies related to communication, collaboration, initiative, and collective decision-making in leaders as facilitators are explored. Based on methodological approaches, effective methods for shaping these skills in young leaders are proposed.